Avaliação de sites sobre a gestão do conhecimento na World Wild Web: um estudo exploratorio - Niraldo Jose do Nascimento (2000)
The work is based on a study of sites regarding management of knowledge in the Word Wide Web, in which he analyzed the way the information has been processed, its availability and distribution over the network, recovery capabilities used interactive processes employees, among others. The goal focuses on the analysis of a sample of pages of information on Knowledge Management ma World Wide Web, trying to identify the main contributions that offer the debate and deepening of the theme by providing articles of external references to other pages. It also analyzes how this information is structured, the ease of access and retrieval of the same, as well as the resources of interactivity with users. For this, an exploratory survey was conducted, using as an assessment tool of WEB pages, constructed with bases in the existing literature and the objects it was intended to achieve. Avaliaçãomdos The results of the study showed that the evaluation process of the WEB pages involves some complexity, we related the extent and dynamics of this information technology. However, if costatou that the difficulties can be overcome by proper delimitation of the study area and the context of the construction of the instruments of analysis process, which should be oriented to the goals and outcomes to be achieved. The study also concluded that the process of evaluation of sites is an important intermediate activity in creating products and services that suistentem actions directed to Knowledge Management and other disciplines or areas of study. One is the costruction of knowledge maps of the Web, which can constitute powerful references and screenplays for external information sources, serving both companies, as practitioners and researchers.